Pengembangan Sistem Pendidikan Salaf Dalam Membentuk Kepribadian Santri Pondok Pesantren Tarbiyatun Nasyi’in Pacul Gowang - Mia Oktaviani; Iva Inayatul Ilahiyah (Menara Tebuireng, 2023)
Forming the personality of Muslim students with activities that build and enliven the values ​​of the salaf Islamic boarding school at the Tarbiyatun Nasyi'in Pacul Gowang Islamic Boarding School. This study uses a descriptive qualitative approach. Qualitative data collection, namely data from interviews, observations, and documentation. Data collection used a research instrument in the form of a list of questions listed in the interview guide. The documentation method is used to collect information about facts in the form of quotations, notes, books and others to complement the information obtained from interviews. . The observation results show that the development of the salaf education system is muadallah, the development of the salaf education system in shaping Muslim personality is based on education, namely prioritizing religious education as a social being who has good morals and Muslim personality. And the supporting and inhibiting factors are the support of strict and painstaking administrators, the application of regulations at Islamic boarding schools, competent ustadz/ustadzah, a supportive environment, and the facilities provided, and hampered by the lack of awareness of the students, the emergence of a feeling of laziness in the students and student background. Keyword: Salaf Education, Muslim Personality